The tongue of Leopard Gecko (Eublepharis macularius): LM, SEM and confocal laser study. (12th September 2019) - Abbate, Francesco; Guerrera, Maria Cristina; Levanti, Maria; Laurà, Rosaria; Montalbano, Giuseppe; Cavallaro, Mauro; Germanà, Antonino
Abstract: The leopard gecko is a crepuscular and insectivorous reptile. The role of the tongue in this reptile is fundamental for the prey capture and ingestion and is not related with eyes cleaning as usual in other geckos. The elongated tongue can be divided into a foretongue with a slightly bifurcated apex and a hindtongue. Scanning electron microscopy demonstrated that several different papillae are present on the dorsal surface, foliate and dome‐shaped in the foretongue, becoming thicker and stouter with reduced interpapillary spaces in the lateral parts. The hindtongue is characterised by wide foliate papillae with indented margins and deep fissures of the mucosa. Light microscopy showed the presence of a stratified slightly keratinized squamous epithelium in the apex of the foretongue, a stratified non‐keratinized squamous epithelium in the fore and in the hindtongue. In the foretongue, numerous muciparous caliciform cells were observed. Moreover, the presence of taste buds on the tongue ventral surface was demonstrated for the first time in this species and the confocal laser study revealed a strong immunoreactivity for the S‐100 protein in the sensory cells. Therefore, the results obtained could give a contribution to the knowledge of the tongue anatomy and are a basis for eventual further studies regarding the feeding habits in a reptile become a popular pet.